How do general practitioners manage patients with cancer symptoms? A video-vignette study - Jiwa, Moyez; Meng, X.; O'Shea, C.; Magin, P.; Dadich, A.; Pillai, V. (2015)
OBJECTIVES: Determine how general practitioners (GPs) manage patients with cancer symptoms. DESIGN: GPs reviewed 24 video-vignettes and case notes on patients with cancer symptoms and indicated whether they would refer the patient and/or prescribe medication, and/or undertake further investigation. According to available guidelines, all cases warranted a referral to a specialist or further investigations. SETTING: Australian primary care sector. PARTICIPANTS: 102 practising GPs participated in this study, including trainees. INTERVENTIONS: The research was part of a larger randomised controlled trial testing a referral pro forma; however, this paper reports on management decisions made throughout the study. PRIMARY AND SECONDARY OUTCOME MEASURES: This paper reports on how the participants would manage the patients depicted in each vignette. RESULTS: In more than one-in-eight cases, the patient was not investigated or referred. Patient management varied significantly by cancer type (p<0.001). For two key reasons, colorectal cancer was the chosen referent category. First, it represents a prevalent type of cancer. Second, in this study, colorectal cancer symptoms were managed in a similar proportion of options-that is, prescription, referral or investigation. Compared with vignettes featuring colorectal cancer participants were less likely to manage breast, bladder, endometrial, and lung cancers with a 'prescription only' or 'referral only' option. They were less likely to manage prostate cancer with a 'prescription only', yet more likely to manage it with a 'referral with investigation'. With regard to pancreatic and cervical cancers, participants were more likely to manage these with a 'referral only' or a 'referral with investigation'. CONCLUSIONS: Some patients may receive a delayed cancer diagnosis, even when they present with typical cancer symptoms to a GP who can access relevant diagnostic tests.